Enhancing Dye-Sensitized Solar Cell Efficiency Using Photosynthetic Pigments from Navicula sp. TAD - Telussa, Ivonne; Maahury, Mirella Fonda; Lilipaly, Eka Rahmat Mahayani Anthonia Putera; Latuihamallo, Threbelin Anacovic Lawdrian (Jurnal Teknik Kimia dan Lingkungan, 2025)
Microalgae Navicula sp. TAD is a microscopic plant that has the potential to serve as an alternative source of pigments, requiring relatively short cultivation time, making it suitable for use as a sensitizer in dye-sensitized solar cells. This research aimed to isolate, characterize, and identify the photosynthetic pigments of Navicula sp. TAD, and subsequently test its photoelectric capability as a sensitizer material in solar cells. The study involved cultivating Navicula sp. TAD cells to obtain biomass, isolating pigments from dry biomass, purifying pigments using column chromatography techniques, characterizing pigments by scanning visible light absorption patterns, and fabricating solar cells with TiO2 paste, followed by testing the photoelectric capabilities of the solar cells. From the research, pigments such as β-carotene, chlorophyll a, xanthophyll, and chlorophyll c were obtained, with chlorophyll a and carotenoid contents of 29.9698 μg/mL and 18.4255 μg/mL, respectively. Solar cells sensitized with photosynthetic pigments showed the best photoelectric performance with crude pigment extract at a concentration of 30×10³ ppm, yielding Short-circuit current density (ISC) 1.93×10⁻⁵ A;  open-circuit voltage (VOC) 0.0465 V; fill factor (FF).58; and efficiency (η) 8.33×10⁻² %. Meanwhile, variations in pigment concentration of chlorophyll and xanthophyll at a ratio of 0:100 yielded ISC 9.96×10⁻⁵ A; VOC 0.1004 V; FF 0.45; and η 7.24×10⁻¹ %.